Parcerias amorosas abusivas: um encontro entre adolescentes na atualidade. - Oliveira, Marina Cunha Barreto de (2020)
The alarming statistic data of violence among love partnerships has promoted the increase of researches about this subject in Brazil and around the world. More recently, some productions have started to focus on the early prevention of these situations and, therefore, to direct their approaches to young people. This research was driven by inquiries, resulting from a professional trajectory crossed by clinical listening and psychoanalysis, in which this theme has become quite frequent. How should an abusive relationship be defined? Why is this kind of relationship so present among teenagers nowadays? Taking these two axes as starting points, the objective is to understand the dynamics of abusive love relationships among adolescents today, through the existing jouissance partnership and the implication of each individual loving choices. We believe that the loving partnership will be constituted between two individuals and their own mode of jouissance. It means that each one takes the other as his or her own jouissance, as if belonged to the other. Therefore, misunderstandings and mismatches arise in the face of individuals who express themselves, their desires and jouissance in a singular and distinct ways. Regarding the methodology, we used the referential and the psychoanalytical method. Taking this approach as a guideline – specifically the contributions of Sigmund Freud and Jacques Lacan – we carry out the analysis of testimonies published by teenagers in digital world about their experiences in abusive relationships. We built the notion that abusive love partnerships can be characterized by a prediction of performances, since the necessary symbolic distance between the individuals do escape in these relationships, bringing out the sharing of an unbridled jouissance in which there is a lack of words and an excess of acts. The intention is that the results obtained from the end of this study may help amplify the knowledge about the logic of abusive loving relationships, as well as, promote a discussion about early intervention practices, adding reflections to the psychoanalytic clinic with teenagers and to future scientific productions.